APOL1 G1 genotype modifies the association between HDLC and kidney function in African Americans - Bentley, Amy R. (BMC Genomics, 2015)
BACKGROUND: Despite evidence of an association between variants at the apolipoprotein L1 gene (APOL1) locus and a spectrum of related kidney diseases, underlying biological mechanisms remain unknown. An earlier preliminary study published by our group showed that an APOL1 variant (rs73885319) modified the association between high-density lipoprotein cholesterol (HDLC) and estimated glomerular filtration rate (eGFR) in African Americans. To further understand this relationship, we evaluated the interaction in two additional large cohorts of African Americans for a total of 3,592 unrelated individuals from the Howard University Family Study (HUFS), the Natural History of APOL1-Associated Nephropathy Study (NHAAN), and the Atherosclerosis Risk in Communities Study (ARIC). The association between HDLC and eGFR was determined using linear mixed models, and the interaction between rs73885319 genotype and HDLC was evaluated using a multiplicative term. RESULTS: Among individuals homozygous for the risk genotype, a strong inverse HDLC-eGFR association was observed, with a positive association in others (p for the interaction of the rs73885319 × HDLC =0.0001). The interaction was similar in HUFS and NHAAN, and attenuated in ARIC. Given that ARIC participants were older, we investigated an age effect; age was a significant modifier of the observed interaction. When older individuals were excluded, the interaction in ARIC was similar to that in the other studies. CONCLUSIONS: Based on these findings, it is clear that the relationship between HDLC and eGFR is strongly influenced by the APOL1 rs73885319 kidney risk genotype. Moreover, the degree to which this variant modifies the association may depend on the age of the individual. More detailed physiological studies are warranted to understand how rs73885319 may affect the relationship between HDLC and eGFR in individuals with and without disease and across the lifespan. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-015-1645-7) contains supplementary material, which is available to authorized users.